Developments in history education in Ghana (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article employs historical records, cultural traditions, and insights from recent interviews with history teachers to trace the beginnings of history teaching and the political landscape that has shaped school history and history curricula in Ghana. The article argues that history education in Ghana has survived the ravages of time, Western historiographical ideals and imperialist ambitions as well as politically motivated legislations and reforms. The article concludes that history education is regaining its grounds in Ghanaian schools and raises implications for teacher education and resource provision in schools. The article contributes to an understanding of the evolution of history education in Ghana and the impact of colonial and political forces on curricula, teaching and learning of African history.
Keywords: Ghana; Education reforms; History curriculum; History education; Teacher education; Schools